THE ROLE OF SOCIAL SERVICES IN COORDINATING EARTHQUAKE AID DISTRIBUTION: A STUDY OF CIANJUR REGENCY’S RESPONSE - Suhara, Ero; Anggoro, Bimo Tri (Journal of Indonesian Rural and Regional Government, 2023)
The problem of this research is the suboptimal distribution of earthquake aid, so that the need for coordination is the most important part. The purpose of this study is to find out, describe and analyze in depth the coordination of the distribution of earthquake aid in Cianjur district. The theory used as an approach to this research problem is the coordination theory from Hasibuan which consists of four principles, namely: unity of action, communication, division of tasks and discipline. The proposition in this study is: coordination of the distribution of earthquake aid in Cianjur district will run optimally if it refers to the principles of unity of action, communication, division of tasks and discipline. The research method used is a descriptive research method, with a qualitative approach, while data is obtained through observation, interviews, and documentation. The results of the study show that the coordination of the distribution of earthquake aid in Cianjur district in its implementation has not run optimally because it has not met the 4 principles of coordination. The efforts made by the social service are to optimize the available resources, continue to increase the involvement of officers and the community, and carry out coordination with various parties.